ChemInform Abstract: Ultralow‐Fatigue Shape Memory Alloy Films. Issue 34 (August 2015) - Chluba, Christoph; Ge, Wenwei; Lima de Miranda, Rodrigo; Strobel, Julian; Kienle, Lorenz; Quandt, Eckhard; Wuttig, Manfred
Abstract Ultralow‐fatigue Ti54Ni34Cu12 shape memory alloy films allow at least 10 million transformation cycles.